2005
DOI: 10.1103/physrevlett.95.164504
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Detachment and Satellite Bead Formation in Viscoelastic Fluids

Abstract: The presence of a very small amount of high molecular weight polymer significantly delays the pinch-off singularity of a drop of water falling from a faucet, and leads to the formation of a long-lived cylindrical filament. In this paper we present experiments, numerical simulations, and theory which examines the pinch-off process in the presence of polymers. The numerical simulations are found to be in excellent agreement with experiment. As a test case, we establish the conditions under which a small bead rem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
128
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 17 publications
10
128
0
Order By: Relevance
“…The front factor obtained from full numerical simulations is approximately 0.7 (cf. Figure 3 in Chen et al 21 ), and this value is also found to agree well with an experimental value of 0.8 obtained from our present experiments, as well as other recent experiments with aqueous polymer solutions 35,48 . When elastic stresses are absent, equation (7) is therefore expected to have a solution of the functional form (in dimensional variables)…”
Section: A Model For Inertio-elastic Pinchingsupporting
confidence: 93%
See 2 more Smart Citations
“…The front factor obtained from full numerical simulations is approximately 0.7 (cf. Figure 3 in Chen et al 21 ), and this value is also found to agree well with an experimental value of 0.8 obtained from our present experiments, as well as other recent experiments with aqueous polymer solutions 35,48 . When elastic stresses are absent, equation (7) is therefore expected to have a solution of the functional form (in dimensional variables)…”
Section: A Model For Inertio-elastic Pinchingsupporting
confidence: 93%
“…Such a description cannot be expected to provide quantitative agreement with experiments or full numerical simulations because it neglects axial variations in the structure of the thread. In particular, for inviscid irrotational flows it has been shown that the simplified one-dimensional Euler equations exhibit a singularity before the point of breakup is reached 48 . Numerical simulations 49,50 show that in fact the free-surface of the droplet close to the singularity overturns.…”
Section: A Model For Inertio-elastic Pinchingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the linear regime (at short times) polymer effects are negligible. Of course this situation changes dramatically in the nonlinear regime (Amarouchene et al (2001); Wagner et al (2005)). The volume V µ of a single bead represents the lower limit for the terminal gobbling drop when reaching the transition to pure jetting and is also compared in figure 13 to the critical gobbling conditions.…”
Section: )mentioning
confidence: 99%
“…[45] These thin filaments are then largely absorbed into the main drops, minimising the formation of satellite droplets and increasing the average droplet size (Figure 3). [46,47] Agricultural spraying is however often carried out at a higher issuing velocity than the Rayleigh regime where the aerodynamic forces dominate (the atomization regime, Figure 4). Here there is complete jet disruption at the nozzle exit, producing droplets with a diameter significantly less than the jet.…”
Section: Agricultural Spraying Overviewmentioning
confidence: 99%